Use of an intragastric trocar to perform a novel stapling procedure for reflux disease - Storm, Andrew C.; AbiMansour, Jad P.; Bofill-Garcia, Aliana; Mahmoud, Tala; Rapaka, Babusai; Lescalleet, Kristin E.; Dayyeh, Barham K. Abu (Endoscopy International Open, 2022)
Background and study aims A percutaneous intragastric trocar (PIT) enables intraluminal use of laparoscopic tools and helps overcome traditional limitations of endoscopy. The aim of this study was to determine the efficacy of using a PIT to perform an anti-reflux stapling procedure.Materials and methods Trocars were placed in four animals and an articulating stapler was used to perform fundoplication under endoscopic guidance. Animals were monitored for 14 days post-procedure. Functional lumen imaging of the esophagogastric junction (EGJ) was performed at baseline, immediately post-intervention, and at 14 days. Results The procedure was successful in all animals who survived to day 14 without distress or significant adverse events. Baseline EGJ distensibility was 5.0 ± 1.2 mm2/mmHg, 2.7 ± 0.7 mm2/mmHg post-procedurally, and 3.0 ± 0.8mm2/mmHg on day 14. Average change in distensibility pre- and post-procedure was –2.3 ± 1.8 mm2/mmHg (95 % confidence interval [CI] –0.5 to 5.1, P = 0.08) while change in pre- and day 14 distensibility was –2.0 ± 1.4 mm2/mmHg (95 % CI –0.1 to 4.2, P = 0.06).Conclusions An intragastric trocar allows for use of large-diameter laparoscopic instruments to safely and effectively perform endoluminal fundoplication with anti-reflux properties that persist for at least 14 days.